Fast Determination of Diclazuril and Toltrazuril Residue Makers in Eggs by Ultra-high Performance Liquid Chromatography-Atmospheric Pressure Chemical Ionization-Triple Quadrupole Mass Spectrometry - ZHANG Haichao, WEI Xinxin, ZHANG Jingwen, JIA Haitao, AI Lianfeng, WANG Jing, HUANG Xuejing, QIN Xiaohang, LIU Baoru (Shipin Kexue)
A comprehensive analytical method was developed for the determination of diclazuril and toltrazuril residue makers in eggs by ultra-high performance liquid chromatography-atmospheric pressure chemical ionization-triple quadrupole mass spectrometry (UPLC-APCI-MS/MS). Samples were extracted with acetonitrile and purified using a PRiME hydrophilic-lipophilic balance (HLB) column. Chromatographic separation was achieved on a ACQUITY BEH C18 column (2.1 mm × 100 mm, 1.7 µm) by gradient elution with a mobile phase composed of acetonitrile and 0.1% formic acid solution. An APCI interface was used as the ion source and the analysis was performed using negative ionization in multiple reaction monitoring (MRM) mode. An internal standard calibration curve method was employed for quantification. The calibration curves were linear in the range of 0.5–200 ng/mL with determination coefficients of more than 0.999 0. The limits of detection (LODs) were 0.5 μg/kg, and the limits of quantization (LOQs) were 2 μg/kg. The average recoveries of the analytes range from 72.8% to 106.5%, with relative standard deviations (RSDs) of 3.2%–8.5%. The developed method is simple, accurate, sensitive, and useful for the rapid detection and confirmation of diclazuride and toltrazuril sulfone residues in eggs.